KONSEP TATA RUANG DI ATAS PERAIRAN PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 85/PUU-XI/2013 - Wiguna, Nicholas Patrick; Warka, Made (Gapenas Publisher, 2025)
According to the Constitutional Court, the Water Resources Law cannot implement and re-enact Law Number 11 of 1974 on Irrigation, which transforms the administration of water resources, including waterways, from privatization. After the Constitutional Court's 85/PUU-XI/2013 judgment, this research examined spatial planning above seas. This study and the Constitutional Court's Decision Number 85/PUU-XI/2013 confirmed that waters are state-controlled common property to be used for the people's benefit in accordance with Article 33 paragraph (2) and paragraph (3) of the 1945 Constitution. Changes in license terminology from